Efficacy of transvaginal sonohysterosalpingography for evaluation of infertile women - Khanum, Mahbuba; Fatima, Parveen; Ishrat, Shakeela; Begum, Taslima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Women with infertility may be benefitted from sonohysterosalpingography (SHSG), a transvaginal ultrasound procedure that uses a contrast medium to assess the endometrial cavity and tubal patency. It could be a safer and more viable alternative to radiographic hysterosalpingography (HSG). The aim of the study was to evaluate the uterine cavity and fallopian tube patency in infertile women by SHSG using transvaginal ultrasound. Methods: The prospective comparative study was carried out in a total of 35 cases of infertile women between the reproductive age of 20-40 years following the inclusion and exclusion criteria, from July 2016 to June 2017. Detailed history and physical examinations were carried out and appropriate management was instituted as per the needs of the individual patient. Results: In the present study, 41.2% of the women belonged to the age range of 25-29 years. Out of 35 women, 50% women were in the state of primary infertility and remaining were in a secondary infertility state. Holding the SHSG both tube blockage as positive findings the sensitivity of SHSG was found at 100%, specificity was 96.88% and accuracy was 97.14%, while positive predictive value was 80.49% and negative predictive value was 100%. Conclusions: Transvaginal SHSG as a first-line method for evaluation of endometrial cavity and tubal patency is effective and time convenient. Before going to the more invasive gold standard methods, i.e. Hysteroscopy and Laparoscopy, this may be a simple, safe, and well-tolerated technique with a low risk of adverse effects and severe complications.